Estrategias metodológicas para el desarrollo del talento creativo en el proceso inter-aprendizaje de los niños/as del primer año de educación básica de la escuela fiscal mixta Lastenia Pesante de Nieto de la ciudad de Santa Rosa periodo lectivo 2013 - 2014. - Álvarez Chica, Josefina Marilú (2014)
The subject of this research has been based development a reality on the urgent need to seek and find an appropriate methodological strategy to provide students with the necessary elements to satisfy his innate curiosity , to give them the opportunity to create and change of get involved , understand and find solutions. Knowing that the first year of basic education is where it provides a full , harmonious development and tools for the later stages of their school life is delivered, you need to understand that the role of the teacher / a is one of the noblest of the society and requires great dedication , preparation and sense of vocation , is when we recognize that through creativity children learn to value yourself , then understand that self-esteem is a necessary condition to implement humane , which It reflected in their values ​​, attitudes, beliefs and emotions.